Penerapan Algoritma C4.5 untuk Memprediksi Penerimaan Calon Pegawai Baru di PT WISE - Fandy Ferdian Harryanto; Seng Hansun (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
A company in general needs employee that have good ability, good manners and also can company. But there are difficulties in finding the qualities of people as a good employee candicacy. That’s why we need a way or method to identify peoples with the potential to become a new employee candidate. C4.5 algorithm can be used to predict and classify new employee candidate that have the potential to get into a corporation by using decision tree according to the data that we have and predict the new employee candidate qualities. According to the testing method called ten-fold cross validation, the accuracy of the prediction for the new employee candidate is 71% by using the built prediction application which implementing C4.5 algorithm.